1992
DOI: 10.1121/1.402628
|View full text |Cite
|
Sign up to set email alerts
|

Auditive and cognitive factors in speech perception by elderly listeners. III. Additional data and final discussion

Abstract: In a previous study [van Rooij and Plomp, J. Acoust. Soc. Am. 88, 2611–2624 (1990)], it was found that speech-perception performance in a sample of elderly subjects tested in the laboratory may be largely determined by two statistically independent components: (1) a major component representing the progressive middle- to high-frequency hearing loss with age and (2) a minor component mainly representing a general decrement in cognitive performance. In the present study, a selected subset of tests used in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(75 citation statements)
references
References 0 publications
3
70
0
2
Order By: Relevance
“…Clinically relevant highfrequency hearing loss has a prevalence of about 55% for 70-79 year olds and of almost 80% in over 80 year olds (Lin, Niparko, & Ferrucci, 2011) making it the third most prevalent chronic health condition facing older adults (Collins, 1997). An adverse effect of elevated highfrequency pure-tone detection thresholds on speech perception has been demonstrated by many studies (Divenyi & Haupt, 1997;Era et al, 1986;Helfer & Wilber, 1990;Humes & Christopherson, 1991;Humes & Roberts, 1990;Humes et al, 1994;Jerger & Chmiel, 1997;Jerger et al, 1991;van Rooij & Plomp, 1990, 1992. However, a decrement in sound detection thresholds is not the only auditory change that occurs with age.…”
Section: Body Functions (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically relevant highfrequency hearing loss has a prevalence of about 55% for 70-79 year olds and of almost 80% in over 80 year olds (Lin, Niparko, & Ferrucci, 2011) making it the third most prevalent chronic health condition facing older adults (Collins, 1997). An adverse effect of elevated highfrequency pure-tone detection thresholds on speech perception has been demonstrated by many studies (Divenyi & Haupt, 1997;Era et al, 1986;Helfer & Wilber, 1990;Humes & Christopherson, 1991;Humes & Roberts, 1990;Humes et al, 1994;Jerger & Chmiel, 1997;Jerger et al, 1991;van Rooij & Plomp, 1990, 1992. However, a decrement in sound detection thresholds is not the only auditory change that occurs with age.…”
Section: Body Functions (B)mentioning
confidence: 99%
“…Cognition has emerged as an important concept in the context of speech perception and comprehension in the last fifty years (e.g., Rabbitt, 1968;Rönnberg et al, 2013;Schneider, 2011;van Rooij & Plomp, 1990, 1992Wingfield, Tun, & McCoy, 2005), partly to account for finding that listeners with similar hearing impairments can vary widely in their level of functioning (Anderson, Parbery-Clark, Yi, & Kraus, 2011;GordonSalant & Fitzgibbons, 1993;Vermiglio, Soli, Freed, & Fisher, 2012). Cognition is a multi-faceted concept and in the following section we will limit the discussion of agerelated cognitive changes to those aspects that are most likely to affect spoken-language comprehension.…”
Section: Attentional Functions (B140)mentioning
confidence: 99%
See 1 more Smart Citation
“…Declines in these aspects of cognitive processing may affect older listeners' capacity to compensate for adverse listening conditions in the perception of speech (compare Cohen, 1987). The first large-scale studies to investigate the contribution of auditory and cognitive factors to speech-processing difficulties found that the degree of audiometric loss accounted for most of the variance in performance, with less variance attributable to general cognitive factors such as processing speed and working memory (Humes, 1996;van Rooij & Plomp, 1992), and reported that the relative balance between auditory and cognitive contributions to speech processing did not change with age (van Rooij & Plomp, 1992). However, the behavioral measures generally used to assess speech intelligibility, such as the repetition of single words, do not necessarily reflect higher level meaning comprehension and may therefore underestimate the role of cognitive factors in the reception of speech in noise.…”
Section: Cognition and Contextual Influences Affecting Speech And Nonmentioning
confidence: 99%
“…unless specific steps are taken to compensate for reduced audibility, audiometric pure-tone thresholds remain the highest predictor of the intelligibility of speech in noise among older and hearing-impaired listeners, accounting for most of the variance in their performance (Jerger et al, 1991;van Rooij and Plomp, 1992;Humes and Dubno, 2010).…”
Section: Introductionmentioning
confidence: 99%